PAPR reduction in F-OFDM system by using cluster scrambling code word shifting / Aidatul Julia Abd Jabar and Azlina Idris - Abd Jabar, Aidatul Julia; Idris, Azlina (Universiti Teknologi MARA, 2021)
Filtered-OFDM (F-OFDM) is one of the proposed candidate for 5G system. In order to support the diversity in services, it requires the capability to support the multiple asynchronous sub-band transmission. However, the multicarrier transmission systems with different sub-carriers are suffer from high Peak-to-Average Power Ratio (PAPR) of the transmit signal. Consequently, the major problem of the F-OFDM system is the high PAPR value in the system that causing the performance degradation due to the various distortions. This paper presents, a method based on manipulation of the codeword by altering its structure known as Cluster Scrambling Codeword (CSC) is proposed to achieve better PAPR reduction. This is a new formulation on bit data sequence shifting technique, which can give better PAPR reduction compared to conventional scheme. The simulations result show that CSC gives 27.08% at 7.0dB which is better PAPR reduction performance compared to the conventional F-OFDM system.